Struktur Komunitas Hama Pemakan Daun Kubis dan Investigasi Musuh Alaminya - YULIADHI, KETUT AYU; SUDIARTA, PUTU (Agrotrop : Journal on Agriculture Science, 2014)
The data concerning the community of pests that eat and destroy cabbage leaves in Bali has not been available yet. However, it is required for the pest control purposes. The aim of the research was to investigate the structure of pest community that eat and destroy cabbage leaves and to find out their natural enemies for controlling the pests. Samples of the pest were collected from the cabbage plants that were treated with insecticide and without insecticide (control). The results show that the phytophage insects that found on both treatments of growing cabbages were Plutella xylostella, Crocidolomia pavonana, Spodoptera litura, Helicoverpa armigera, Chrysodiexis orichalcea, and Aphis brassicae. Natural enemies that found on that area were parasitoid larva Plutella Diadegma semiclausum and predator Crocidolomia pavonana, Sycanus dichotomus pdf (secured).
Keywords: Cabbage , Plutella xylostella, Crocidolomia pavonana, Diadegma semiclausum, Sycanus dichotomus